PENGARUH MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA DINAS PENGENDALIAN PENDUDUK, KB, PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN KAUR - Sri Handayani; Ahmad Soleh; Ike Wulandari (Creative Research Management Journal, 2020)
The purpose if this study is to describe and analyze of motivation and leadership on theperformance of employees in the Department of PP (Population Control), KB (Family Planning),PP (Women's Empowerment) and PA (Children Protection) in Kaur Regency. This type ofresearch uses quantitative descriptive. The sampling technique used census techniques of 49respondents. Research analysis using multiple linear regression analysis.Based on thediscussion, it can be concluded that motivation does not influence the performance of employeesin the Department of PP, KB, PP and PA in Kaur Regency. This is evidenced by the calculated t count obtained for 1,640. While the value of t table is 2.013, hence t count< t table which results in H0is accepted and Ha is rejected, which means the research hypothesis is rejected. Leadershipinfluences the performance of employees in the Department of PP, KB, PP and PA in KaurRegency. This is evidenced by the calculated t count obtained of 5.700. While the value of t table is2.013, hence t count> T table which results in H0 is rejected and H1 is accepted, which means theresearch hypothesis is accepted.